A new acridone with antifungal properties against Candida spp. and dermatophytes, and antibiofilm activity against C. albicans - de Oliveira, D. B.C.; Silva, L. B.; da Silva, B. V.; Borges, T. C.; Marques, B. C. [UNESP]; dos Santos, M. B. [UNESP]; de Oliveira, L. F.; Bolzani, V. S. [UNESP]; Rodrigues, A. R.A.; Regasini, L. O. [UNESP]; Andrade, A. A. (Oxford University Press (OUP), 2019)
Aim: The increase in the number of fungal infections worldwide, coupled with the limitations of current antifungal chemotherapy, demand the development of safe and effective new antifungals. Here, we presented the synthesis of a novel acridone (M14) and its antifungal properties against Candida and dermatophytes species. Methods and Results: A series of 17 acridones was designed, synthesized and tested for its antifungal activity. The minimum inhibitory concentration (MIC) was determined by the broth microdilution method. Only the acridone M14 showed growth-inhibitory activity against reference strains and clinical isolates of Candida and dermatophytes, with MIC range of 7·81–31·25 µg ml−1. Moreover, M14 exhibited fungicidal activity and prevented biofilm formation by C. albicans as well as reduced the viability of preformed biofilms, even at sub-MICs. The confocal laser scanning microscopy analysis revealed that C. albicans hyphal growth was completely inhibited in the presence of M14. Similarly, there was a severe inhibition on hyphal growth of Trichophyton rubrum. We also found that M14 has relatively low toxicity to human fibroblasts. Conclusions: The new acridone M14 has antifungal properties against Candida spp. and dermatophytes, and antibiofilm activity against C. albicans. In addition, M14 is relatively selective to fungal cells compared to human normal cells. Significance and Impact of the Study: Because of its in vitro antifungal activity, anti-Candida biofilm effect and moderate cytotoxicity towards normal human cell, M14 may serve as a valuable lead compound to develop a new antifungal agent.
Keywords: acridones; antibiofilm; antifungal activity; Candida spp.; cytotoxicity; dermatophytes